A superstructure nano-wave absorbing coating and preparation method thereof

The single dispersed absorbing material with regular superstructures was prepared and self-assembled through the hard template method, which solved the problems of poor absorption capacity and high density of existing absorbing materials in the low-frequency band, and achieved efficient radar wave absorption and multi-band camouflage Invisible effect.

CN117812904BActive Publication Date: 2024-12-17新兴际华(上海)工程科技研究院有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311818311.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2024-12-17
Estimated Expiration
2043-12-27

AI Technical Summary

Technical Problem

The existing wave absorbing materials have poor absorption capacity in the low frequency band and are too dense to form regular superstructures, and cannot effectively improve radar stealth and electromagnetic protection capabilities.

Method used

The hard template method is used to prepare monodispersed ferrite absorbing materials with uniform size and hollow structures, and form a regular periodic arrangement superstructure through self-assembly, combining the interaction of electromagnetic waves to improve the absorption effect, and in the visible and infrared bands Provides adjustable response.

Benefits of technology

It achieves excellent radar wave absorption effect and multi-band camouflage stealth, reducing material density and improving electromagnetic protection capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117812904B_ABST
    Figure CN117812904B_ABST
Patent Text Reader

Abstract

The present invention discloses a superstructure nano-wave absorbing coating and a preparation method thereof. The superstructure nano-wave absorbing coating is a superstructure with regular periodic arrangement formed by self-assembly of a monodisperse absorbing material with a hollow structure. The preparation method of the monodisperse absorbing material with a hollow structure is as follows: 1) surface modifying monodisperse nano-microspheres as a hard template; 2) mixing the absorbing material nanoparticles with the hard template; 3) coating the composite microspheres obtained in step 2 by in-situ synthesis of a skeleton material; 4) removing the hard template to form a hollow structure. The present invention prepares a monodisperse ferrite absorbing material with a hollow structure by a hard template method, and further uses self-assembly to obtain a preparation and assembly method of a densely packed and regularly arranged superstructure absorbing structure, which can achieve excellent radar wave absorption effect and provide adjustable response in the visible light or infrared light band.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of camouflage and stealth, and specifically relates to a superstructure nano-wave absorbing coating and a preparation method thereof. Background Art

[0002] With the rapid development of battlefield detection technology, the requirements for radar stealth capabilities are getting higher and higher. At the same time, with the gradual popularization of new-generation communication technologies represented by 5G, the requirements for the electromagnetic protection capabilities of electronic devices are getting higher and higher. Therefore, both the military and civilian markets have put forward new requirements for the performance of absorbing materials. Traditional absorbing materials are mainly magnetic materials represented by carbonyl metal powders and micron metal powders, and carbon materials represented by carbon black and carbon nanotubes. The former has a better absorbing effect, but the density is too high; while the latter has poor absorbing ability in the low frequency band. Therefore, the development of new absorbing materials with higher absorbing performance and lower material density is one of the important directions in this field.

[0003] Developing absorbing materials with hollow structures is one of the technologies that can effectively reduce the specific gravity of materials and improve absorbing performance. Many documents and patents have adopted this strategy to improve the synthesis of absorbing materials.

[0004] CN 110564365 A discloses a method for preparing a graphene foam composite material loaded with magnetic hollow nanospheres. The method uses graphene oxide, hexadecyltrimethylammonium bromide and metal salt as raw materials, adopts a solvent thermal method to prepare a three-dimensional mesh graphene oxide foam loaded with glycerate metal salt; then freeze-drying, roasting and reducing in a protective atmosphere, and obtaining a graphene foam composite material loaded with magnetic hollow nanospheres in situ.

[0005] CN 108124413 B discloses a porous hollow iron nano-spherical electromagnetic wave absorbing material and a preparation method and application thereof. Precursor salts such as ferric nitrate and surfactants such as polyvinyl pyrrolidone are dissolved in an alcohol solvent, and then a small amount of deionized water is added to obtain a precursor by solvent thermal reaction, which is then calcined and reduced in a hydrogen atmosphere to obtain porous hollow iron nano-spheres by direct reduction at 400-500°C.

[0006] In the above two invention patents, the prepared hollow materials are of uneven size and exist in a state of irregular stacking. They cannot form a regular arrangement structure through self-assembly, and thus cannot form a superstructure with unique electromagnetic regulation effect. Summary of the invention

[0007] In view of the defects of the prior art, the inventors of the present invention adopt a specific synthesis process to prepare a magnetic material with uniform size and hollow structure, and further form a superstructure with regular periodic arrangement through self-assembly. The interaction between the superstructure and electromagnetic waves is used to enhance the absorption effect, and an adjustable response effect in the visible and infrared bands is added, which can be used as an effective lightweight and high-efficiency absorber.

[0008] The present invention provides a method for preparing a monodisperse ferrite absorbing material with a hollow structure by a hard template method, and further obtaining a preparation and assembly method of a densely packed and regularly arranged superstructure absorbing structure by self-assembly, which can achieve excellent radar wave absorption effect and provide adjustable response in the visible light or infrared light band.

[0009] In order to achieve the above-mentioned purpose, the present invention adopts the following technical scheme:

[0010] In a first aspect, the present invention provides a monodisperse absorbing material with a hollow structure and a preparation method thereof.

[0011] The monodisperse wave absorbing material with a hollow structure provided by the present invention is prepared according to a method comprising the following steps:

[0012] Step 1: Surface-modify the monodisperse nanomaterial to obtain a modified template as a hard template;

[0013] Step 2: mixing the absorbing material nanoparticles with the hard template to obtain composite particles;

[0014] Step 3: coating the composite particles obtained in step 2 by in-situ synthesis of a skeleton material;

[0015] Step 4: Remove the hard template to form a hollow structure, the outer layer of which is a skeleton structure formed by the skeleton material, and the inner wall of the shell is an absorbing material layer.

[0016] In step 1 of the above method, the nanomaterial may be nano-microspheres.

[0017] In step 1 of the above method, the shape of the nanomaterial can be one of a sphere, a cube, an ellipsoid, a regular octahedron, and a regular dodecahedron.

[0018] In step 1 of the above method, the purpose of the surface modification is to allow the absorbing material nanoparticles to better adhere to the surface of the monodisperse nanomaterial; the specific method of the surface modification is to use a specific surfactant (sodium polystyrene sulfonate) or salt (sodium chloride) to mix with the monodisperse nanomaterial, thereby achieving the modification of the monodisperse nanomaterial.

[0019] Furthermore, the mass ratio of the sodium polystyrene sulfonate or salt (such as sodium chloride) to the monodisperse nanomaterial is (0.001-0.1):1, preferably (0.001-0.005):1.

[0020] Furthermore, the nanomaterial can be selected from nano-microspheres formed by at least one of the following materials: polystyrene, silicon dioxide, and polymethyl methacrylate.

[0021] The size of the nano-microspheres is 0.1-50 microns, and the coefficient of variation of particle size distribution is less than 5%.

[0022] In step 2 of the above method, the volume ratio of the absorbing material nanoparticles to the hard template is 1:10-1:1000, preferably 1:10-1:100.

[0023] The component of the absorbing material is selected from at least one of the following: carbonyl iron, carbonyl nickel, ferroferric oxide, ferrous oxide, nickel ferrite, cobalt ferrite, and manganese ferrite.

[0024] In step 2 of the above method, the size of the absorbing material is 5-50 nanometers, and can further be 10-20 nanometers.

[0025] In step 2 of the above method, the absorbing material nanoparticles are mixed with the hard template, and the surface of the hard template is modified to have a charge opposite to that of the absorbing material nanoparticles, and the nanoparticles are uniformly attached to the surface of the hard template by utilizing the principle of "opposites attract".

[0026] In step three of the above method, the framework material is selected from at least one of the following: silicon dioxide, titanium dioxide, and zirconium dioxide.

[0027] In step three of the above method, a modified Stober method is used to in-situ coat the composite microspheres obtained in step two with a skeleton material.

[0028] In step 4 of the above method, the hard template can be removed by high temperature baking or etching.

[0029] The particle size of the monodisperse wave absorbing material with a hollow structure prepared by the above method is 0.1-50 microns.

[0030] In a second aspect, the present invention provides a superstructure nano-wave absorbing coating.

[0031] The superstructure nanometer wave-absorbing coating provided by the present invention is a superstructure with regular periodic arrangement formed by self-assembly of the monodisperse wave-absorbing material with a hollow structure prepared by the present invention.

[0032] Specifically, the method for preparing the superstructure nano-wave absorbing coating comprises the following steps:

[0033] Step a: dispersing a monodisperse absorbing material having a hollow structure in a solvent, and further mixing it with a base material of the absorbing coating;

[0034] Step b: applying the above mixture on the surface of the protected object, placing it in an oven to dry, and allowing it to stand for a long time;

[0035] Step c: obtaining the microwave absorbing coating by photocuring or thermal curing.

[0036] In step a of the above method, the base material of the radar absorbing coating may be one of polyurethane or epoxy resin coating slurry.

[0037] In step a of the above method, the ratio of the monodisperse absorbing material with a hollow structure to the base material of the absorbing coating is 1:100-1:1, preferably 1:10-1:1.

[0038] In step a of the above method, the solvent is water and ethanol or a mixture of the two.

[0039] In step b of the above method, the material of the surface of the protected object may be one of metal, plastic, cloth, and ceramic.

[0040] Furthermore, the thickness of the superstructure nano-wave absorbing coating may be 5-5000 microns, preferably 800-200 microns.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] The hollow structure can not only effectively reduce the density of the material, but also guide the electromagnetic waves to reflect multiple times inside the material to achieve rapid attenuation of the electromagnetic wave energy; the periodically arranged superstructure can achieve a unique interaction with electromagnetic waves through Bragg diffraction and other methods, not only improving the radar wave absorption capacity of a specific band, but also producing specific reflections in the visible light or infrared light bands, achieving multi-band camouflage and stealth effects. In addition, according to electromagnetic theory, the direction of electromagnetic waves on the surface of a material depends on the intrinsic dielectric constant and magnetic permeability parameters of the material, and the hollow structure can introduce air components into the material, making the material's comprehensive impedance closer to the impedance of free space, thereby reducing the difficulty of electromagnetic waves entering the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 A schematic diagram of the preparation process of the hollow structured monodisperse absorbing material provided by the present invention.

[0044] Figure 2 This is a hollow absorber with a self-assembled stacking structure formed in the absorbing coating of Example 1 (SEM photo).

[0045] Figure 3This is a reflection spectrum diagram of the absorbing coating in Example 1 in the visible-infrared band.

[0046] Figure 4 This is the radar reflectivity attenuation curve of the absorbing coating in Example 1. DETAILED DESCRIPTION

[0047] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0048] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0049] The modified Stober method described in the following examples can be found in the following literature:

[0050] DOI: 10.13801 / j.cnki.fhclxb.20230105.003,

[0051] or DOI: 10.3321 / j.issn:1005-023X.2008.12.030.

[0052] Embodiment 1:

[0053] Polystyrene nanospheres with a diameter of 230 nanometers and a variation value of 3% were mixed with sodium polystyrene sulfonate (the ratio of the two was 200:1) to achieve surface modification of polystyrene nanospheres; the modified nanospheres (hard templates) were ultrasonically mixed with ferroferric oxide nanoparticles (particle size of 10 nanometers) dispersed in an aqueous solution, and the volume ratio of the two (solid powders) was 10:1; then the precipitate was dispersed in an ethanol solution by centrifugal separation, and a silica shell was in situ generated on the surface of the polystyrene@ferroferric oxide nanospheres by the modified Stober method (using tetraethyl silicate) to obtain polystyrene@ferroferric oxide@silica nanospheres. Finally, the central polystyrene template was removed by calcination at 600°C in a muffle furnace to obtain hollow ferroferric oxide@silica nanospheres (particle size of 270±15 nanometers).

[0054] The hollow ferroferric oxide@silica nanospheres are dispersed in ethanol and mixed with a photocurable coating base material (wherein the volume ratio of the hollow ferroferric oxide@silica nanospheres to the photocurable coating base material is 1:5) to form an absorbing coating; after the absorbing coating is applied on the surface of the protected object, the ethanol is evaporated by drying at 90°C and the coating is left to stand for more than 10 minutes; finally, the absorbing coating (the coating thickness is 800 microns) is formed after UV curing.

[0055] The light-curable coating used is not limited to a specific composition or formula, and any coating that can form a coating by light curing is acceptable.

[0056] Figure 2 The hollow absorber with self-assembled stacking structure formed in the absorbing coating of Example 1 (SEM photo). Figure 2 It can be seen that the polystyrene nanospheres used are of uniform size, about 230 nanometers, and thus self-assemble into a regularly arranged structure under an electron microscope.

[0057] Figure 3 is the reflection spectrum of the absorbing coating in Example 1 in the visible-infrared band. Figure 3 It can be seen that the absorbing coating formed by the self-assembly of nano-microspheres has multiple reflection peaks formed by Bragg diffraction in the visible-infrared band, and the main peak is at around 700nm, so it appears red when observed with the naked eye; several peaks in the infrared band indicate that it also responds to infrared light and can perform infrared camouflage signals as needed.

[0058] Figure 4 is the radar reflectivity attenuation curve of the absorbing coating in Example 1. Figure 4 It can be seen that the absorbing coating has a certain electromagnetic wave absorption ability in the range of 2 to 18 GHz.

[0059] Embodiment 2:

[0060] Silica nanospheres with a diameter of 800 nanometers and a variation value of 3.5% were mixed with sodium polystyrene sulfonate (the ratio of the two was 1000:1) to achieve surface modification of the silica nanospheres; the modified nanospheres (hard template) were mixed with iron oxide nanoparticles (particle size of 15 nanometers) dispersed in an aqueous solution by ultrasonic mixing, and the volume ratio of the two (solid powder) was 20:1; then the precipitate was dispersed in an ethanol solution by centrifugal separation, and a titanium dioxide shell was in situ generated on the surface of the silica@iron oxide nanospheres by the modified Stober method (using tetraethyl titanate), and silica@iron oxide@titanium dioxide nanospheres were obtained. Finally, the central silica template was removed by etching in a 10% hydrofluoric acid solution for 4 hours to obtain hollow iron oxide@titanium dioxide nanospheres (particle size of 870±30 nanometers).

[0061] The hollow ferric oxide @ titanium dioxide nanospheres are dispersed in deionized water and mixed with a heat-curing coating base material (wherein the volume ratio of the hollow ferric oxide @ titanium dioxide nanospheres to the heat-curing coating base material is 1:9) to form an absorbing coating; after the absorbing coating is applied to the surface of the protected object, the ethanol is evaporated by drying at 60°C and the coating is allowed to stand for more than 30 minutes; finally, the absorbing coating is formed after being cured by heating at 90°C for 10 minutes (the coating thickness is 1300 microns).

[0062] The heat curing coating used is not limited to a specific composition or formula, and any coating that can form a coating by photothermal curing can be used.

[0063] Embodiment 3:

[0064] Silica particles with a diameter of 30 microns and a variation value of 5% were mixed with sodium chloride (the ratio of the two was 500:1) to achieve surface modification of the silica particles; the modified silica particles (hard template) were ultrasonically mixed with nickel ferrite nanoparticles (particle size of 20 nanometers) dispersed in an aqueous solution, and the volume ratio of the two was 100:1; then the precipitate was dispersed in an ethanol solution by centrifugal separation, and a zirconium dioxide shell was in situ generated on the surface of the silica@nickel ferrite particles by the modified Stober method (using zirconium tetraethoxide) to obtain silica@nickel ferrite@zirconium dioxide particles. Finally, the central silica microsphere template was removed by NaOH etching in a muffle furnace to obtain hollow nickel ferrite@zirconium dioxide particles (particle size of 30±0.08 microns).

[0065] The hollow nickel ferrite @ zirconium dioxide particles are dispersed in methanol and mixed with a photocurable coating base material (wherein the volume ratio of the hollow nickel ferrite @ zirconium dioxide particles to the photocurable coating base material is 1:2) to form an absorbing coating; after the absorbing coating is applied to the surface of the protected object, the ethanol is evaporated by drying at 70°C and the coating is left to stand for more than 10 minutes; finally, the absorbing coating (the coating thickness is 2000 microns) is formed after UV curing.

Claims

1. A superstructure nano-absorbent coating, which is a superstructure with regular periodic arrangement formed by self-assembly of a monodisperse absorbing material with a hollow structure; The method for preparing the monodisperse wave absorbing material with a hollow structure comprises the following steps: Step 1: Surface-modify the monodisperse nanomaterial to obtain a modified template as a hard template; Step 2: mixing the absorbing material nanoparticles with the hard template to obtain composite particles; Step 3: coating the composite particles obtained in step 2 by in-situ synthesis of a skeleton material; Step 4: remove the hard template to form a hollow structure, the outer layer of which is a skeleton structure formed by the skeleton material, and the inner wall of the shell is an absorbing material layer; In the step 1, the surface modification is performed using sodium polystyrene sulfonate or sodium chloride; In the step 1, the nanomaterial is nanospheres; the nanospheres are selected from nanospheres formed of at least one of the following materials: polystyrene, silicon dioxide, polymethyl methacrylate; the size of the nanospheres is 0.1-50 microns, and the coefficient of variation of the particle size distribution is less than 5%; In the step 2, the volume ratio of the absorbing material nanoparticles to the hard template is 1:10-1:1000; In the step 2, the component of the absorbing material is selected from at least one of the following: carbonyl iron, carbonyl nickel, ferroferric oxide, ferrous oxide, nickel ferrite, cobalt ferrite, and manganese ferrite; In the step 2, the size of the nanoparticles of the absorbing material is 5-50 nanometers; In the step 3, the framework material is selected from at least one of the following: silicon dioxide, titanium dioxide, and zirconium dioxide; In the step three, the composite microspheres obtained in step two are in situ coated with a skeleton material using a modified Stober method.

2. The superstructure nano-wave absorbing coating according to claim 1, characterized in that: In the step 4, the hard template is removed by high temperature baking or etching.

3. The superstructure nano-wave absorbing coating according to claim 1 or 2, characterized in that: The method for preparing the superstructure nano-wave absorbing coating comprises the following steps: Step a: dispersing the monodisperse absorbing material with a hollow structure in a solvent, and further mixing it with a base material of the absorbing coating; Step b: coating the mixture obtained in step a on the surface of the protected object, placing it in an oven to dry and remove the solvent, and allowing it to stand for a long time; Step c: obtaining the microwave absorbing coating by photocuring or thermal curing.

4. The superstructure nano-wave absorbing coating according to claim 3, characterized in that: In the step a, the base material of the radar absorbing coating is one of polyurethane or epoxy resin coating slurry; Or, in step a, the solvent is one or a mixture of water and ethanol; Or, in the step a, the ratio of the monodisperse absorbing material with a hollow structure to the base material of the absorbing coating is 1:100-1:

1.

5. The superstructure nano-wave absorbing coating according to claim 1, characterized in that: The thickness of the superstructure nano-wave absorbing coating is 5-5000 microns.